023 ACUTE CORONARY SYNDROME: CODING CHALLENGES AND POTENTIAL FINANCIAL LOSS TO SECONDARY CARE, A RETROSPECTIVE AUDIT. (24th May 2013) - Natarajan, V D; Bunker, N; Purcell, M; Cadman, J; Kumar, G
Abstract : Introduction: Clinical coding is the translation of a diagnostic or procedural term, as written by a clinician in the patient record, into an α-numeric code (with associated code description), using the statistical classifications International Statistical Classification of Diseases and Related Health Problems (Tenth Revision)(ICD-10) and OPCS-4, Office of Population, Censuses and Surveys Classification of Interventions and Procedures (4th revision). Acute coronary syndrome (ACS) is a spectrum of disease process that may indicate either an unstable angina (UA) coded as I20 or two different presentations of myocardial infarction namely non ST elevation myocardial infarction (NSTEMI) or ST elevation myocardial infarction (STEMI) coded as I21 with an inclusion of a fifth digit giving further information of particular type (I21.00, I21.01 etc). Current clinical and coding practice was reviewed through retrospective audit. Methods: Retrospective data of all patients hospitalised with chest pain of any cause during October 2011 was reviewed (n 185). The accuracy of clinical diagnosis and clinical coding was evaluated utilising the Patient Administration System (PAS) data, by reviewing all electronic discharge letters (EDL) and whenever necessary the full medical records. The subset of patients with inaccurate diagnosis or coding was further analysed to establish financial gain or loss. Results: Out of the 185 patient episodes 60 (32.4%) were secondary to ACS. 13.3% of the ACS cohort had inaccurate clinical coding as a result of incomplete EDL diagnosis resulting in inaccuracy and further assessment confirmed a total estimated loss of income of £7787. The remaining 52 (86.67%) episodes were appropriately coded as per standards in 2011. Conclusions: This retrospective study demonstrates a considerable financial loss within the month audited. Assuming this is reflective of practice at the time this translates to a potential significant financial loss for the trust for the financial year 2011/2012. Management of UA or NSTEMI are mostly the same as per current clinical practice and guidance, however the treatment tariffs vary significantly. Inaccuracy, of documentation of clinical diagnosis may result in ambiguity and inappropriate or inaccurate coding and subsequent either over or underpayment. Most of the trainees are unaware of these and senior input in verification of discharge diagnosis is diminishing and is mostly inadequate. A larger prospective audit from multiple sites to increase validity and reliability is proposed. Dissemination of findings and increasing awareness of the clinical and financial importance of accurate documentation and coding for patients, trusts and commissioners is recommended.